Unlocking Global Opportunities : The Aid for Trade Program of the World Bank Group - World Bank (Washington, DC, 2014)
Aid for trade is a means to help developing countries, especially low-income countries, integrate into the world economy as a way to spur growth. The recent financial crisis and global recession have, if anything, made aid for trade more urgent. Trade worldwide is likely to contract in 2009. It has become a main channel through which recessionary impulses from the United States and Europe are transmitted to developing countries. But these forces will sooner or later reverse: when growth does resume, trade is likely to be a leading source of demand. Helping countries to take full advantage of the global recovery, whenever it comes, has become a priority for rekindling growth, as well as sustaining rising incomes into the future. The aid-for-trade program of the World Bank Group, as with other donors, is multifaceted. It goes beyond concessional lending commitments to low-income countries (the conventional definition used by the OECD/WTO). It also involves World Bank non-concessional trade-related lending to middle-income countries. Promoting trade-led growth in middle-income countries creates market opportunities for neighboring low-income countries, to say nothing of the benefits such opportunities entail for trade creation worldwide. Moreover, investments by the World Bank's private sector arm, the International Finance Corporation (IFC), in private sector activities can also generate trade and growth by expanding productive capacity in tradable goods. IFC private investments in the financial sector have also been instrumental in overcoming crisis induced constraints on trade finance. Finally, focusing solely on financial flows would miss the important role of policy advice and technical assistance embodied in studies and capacity-building efforts of donors.